2002
DOI: 10.1016/s0735-1097(01)01779-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of normalized myocardial perfusion after successful angioplasty in acute myocardial infarction

Abstract: Abnormal myocardial perfusion is present in most patients following primary or rescue PCI in AMI, despite restoration of brisk epicardial coronary flow. In high risk patients achieving TIMI-3 flow after intervention, the myocardial blush score may be used to stratify prognosis into excellent, intermediate and poor survival. Further study is warranted to examine whether adjunctive mechanical or pharmacologic strategies can further improve myocardial perfusion and survival of patients with acute myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
218
3
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(236 citation statements)
references
References 19 publications
9
218
3
6
Order By: Relevance
“…2 Both distal embolisation and reduced tissue perfusion (impaired ST segment resolution and angiographic myocardial blush grade) after primary PCI have been associated with substantial increases in mortality and morbidity. [2][3][4] Thrombus aspiration during primary PCI has been thought to be an effective method for reducing distal embolisation and improving microvascular perfusion. The Thrombus Aspiration during Percutaneous Coronary Intervention in Acute Myocardial Infarction Study (TAPAS), 5 which enrolled 1071 patients, showed that routine thrombus aspiration improved the primary outcome of microvascular perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…2 Both distal embolisation and reduced tissue perfusion (impaired ST segment resolution and angiographic myocardial blush grade) after primary PCI have been associated with substantial increases in mortality and morbidity. [2][3][4] Thrombus aspiration during primary PCI has been thought to be an effective method for reducing distal embolisation and improving microvascular perfusion. The Thrombus Aspiration during Percutaneous Coronary Intervention in Acute Myocardial Infarction Study (TAPAS), 5 which enrolled 1071 patients, showed that routine thrombus aspiration improved the primary outcome of microvascular perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, impaired regional perfusion and microvascular or endothelial dysfunction within the previously ischemic myocardium after revascularization therapy also produce the no-reflow phenomenon, which may lead to increased infarct size, contractile dysfunction, higher incidence of complications, and poor clinical outcome [1][2][3][4] . Prevention and treatment of the no-reflow phenomenon have been a worldwide challenge in this reperfusion times.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of microvascular tissue reperfusion, such as the degree of ST-segment resolution or angiographic myocardial blush grade, have been shown to predict the rate of death after primary PCI. 2,3 Removal of the thrombus by manual thrombectomy before stent deployment has the potential of reducing distal embolization and improving microvascular perfusion. Small, randomized trials of thrombectomy have shown improvements in markers of tissue reperfusion.…”
mentioning
confidence: 99%